A reflective study on adopting inquiry-based science teaching methods - Benjamin Aidoo (Disciplinary and Interdisciplinary Science Education Research)
Abstract This paper is based on a reflection of my interest in science, views about science, science teacher education, and science teaching experiences. Using the self-study, I explored how my training in science education has influenced my interest in teaching science using inquiry-based learning. Anutoethnography approach was systematically used to describe and analyze my experiences through the transformation to identify my professional learning identity. Multiple data sources from academic learning, teaching experiences, workshops, and documents from lesson plans and curricula documents enabled me to understand my professional practice and build professional identity. The findings showed that teachers professional learning positively impacts their beliefs about IBL. Teachers with positive attitudes toward adopting IBL approach as facilitators are supported by their previous learning experiences. Teachers experiences in adopting IBL are influenced by their professional growth through their learning experiences and involvement in a collaborating learning community. in addition, teacher-reflective learning enables them to develop new PCK that allows them to use prior experiences to adopt strategies that could motivate students to engage in learning activities that enhance their thinking to solve problems in their inquiry lessons. Further, classroom discussions and reflections with students impact their understanding of concepts for knowledge construction. These findings suggest that engaging students in inquiry learning can be an effective way for teachers to develop their competencies to teach science, especially when responding to students questions. The findings highlight the need for integrating IBSE in teacher education programs focusing on the development of pedagogy, content and knowledge. Such development for teacher preparation could support the future teachers, in-service teachers for IBL induction and PCK for ongoing reflections for improvement in their science classroom practices.